Peningkatan Kemandirian Ekonomi Perempuan Madura Desa Tempurejo, Kecamatan Tempurejo, Kabupaten Jember melalui Kelompok Literasi Perempuan - Setyari, Agustina Dewi; Husniah, Furoidatul; Angelina, Dewi (Proceedings of Annual Conference on Community Engagement, 2018)
Low levels of education and high rates of early marriage for women have serious implications for women's economic independence. This made some lecturers in Unej challenged to carry out community service related to efforts to increase women's economic independence through women's literacy groups in Tempurejo Village. To mediate their needs, activities are needed to increase knowledge and insight related to women's economic independence. The activity was realized in the form of Community Service through women's school literacy as an effort to provide awareness about the importance of economic independence for women. In community service carried out by the dedication team from the Faculty of Cultural Sciences and FKIP Unej, an informal school was held for women in the village of Tempurejo. Therefore, the formulation of the problem in community service is (a) how to make women aware in the village of Tempurejo about the importance of economic independence for women? (b) What is the follow-up of the informal school?